Cardiac Inflammatory Myofibroblastic Tumor: A Multiparametric Imaging Approach. (September 2019) - D'Angelo, Tommaso; Mazziotti, Silvio; Inserra, Maria Cristina; De Luca, Francesco; Agati, Salvatore; Magliolo, Emilia; Pathan, Faraz; Blandino, Alfredo; Romeo, Placido
Abstract : Supplemental Digital Content is available in the text.